Current and emerging trends in acquaculture : proceedings of the National Seminar on Current and Emerging Trends in Aquaculture and its Impact on Rural Development, 14-16 February 1995 - National Seminar on Current and Emerging Trends in Aquaculture and its Impact on Rural Development (1995 : Orissa University of Agriculture and Technology); Thomas, P. C., 1939-; Orissa University of Agriculture and Technology (Delhi : Daya Pub. House, 1998)
Papers presented at the seminar organized by Orissa University of Agriculture and Technology; in the Indian context.
Includes bibliographical references and indexes.
Keywords: Aquaculture -- India -- Congresses